Remote Teaching – a Challenge for School Education - Kuźmińska-Sołśnia, Beata (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2020)
The article deals with the challenges facing education in the 21st century. The current situation in Poland has obliged many teachers to use remote working tools. Concern for the health of students and teachers has forced the implementation of distance learning at all stages of education. The main aim of the article is to present the direction of changes, both in the technology and school education sectors, as well as the analysis of research conducted among primary school students on the implementation of remote education. Will the distance learning experience gained in recent months change the attitude of teachers and students to the teaching and learning process, and will the use of digital technologies change the educational environment preparing students for the challenges of the 21st century? What steps should be taken in schools to use available technologies in a more innovative and creative way? The clues for further changes in education should be the reflection of the whole school community on the findings of research data and the analysis of remote learning.